Early rehabilitation of cancer patients after endoprosthetic reconstruction following resection of the lower extremity long bones - A. V. Bukharov; E. V. Filonenko; D. A. Erin; V. A. Derzhavin; A. V. Yadrina; A. M. Shatalov; D. O. Elkhov; M. D. Aliev (Сибирский онкологический журнал, 2022)
Aim of the study: to conduct a systematic analysis of the data available in the modern literature, prognostic factors, and modern methods of rehabilitation of cancer patients after endoprosthetic reconstruction following resection of the lower extremity long bones. Material and methods. We assessed reports of clinical trials published over the past 10 years, which evaluated prognostic factors, rehabilitation programs for cancer patients who underwent endoprosthetic reconstruction following resection of the lower extremity long bones, depending on the location and size of the implant and the age of the patient. The review also evaluated various prognostic factors that affected functional recovery following resection of the lower extremity long bones. Results. Findings that helped in choosing the best option for surgical treatment, thus providing the best quality of life in the postoperative period, were published. Conclusion. Further studies are needed to optimize rehabilitation techniques and develop new algorithms for the treatment of cancer patients who underwent endoprosthetic reconstruction following resection of the lower extremity long bones.